Narwhal and Jelly. 1, Narwhal's Otter Friend - Clanton, Ben, 1988- (New York, New York : Scholastic, Inc., 2020)
b
Narwhal is really awesome -- Narwhal's pod of awesomeness -- Narwhal and the best book ever.
"A Junior Library Guild selection"--Page 4 of cover.
Keywords: Narwhal -- Juvenile fiction; Jellyfishes -- Juvenile fiction; Marine animals -- Juvenile fiction; Friendship -- Juvenile fiction; Sea stories